NHI-PharmaCloud in Taiwan—A preliminary evaluation using the RE-AIM framework and lessons learned. Issue 10 (October 2015) - Huang, San-Kuei; Wang, Pen-Jen; Tseng, Wen-Fuh; Syu, Fei-Kai; Lee, Miaw-Chwen; Shih, Ru-Liang; Sheen, Mao-Ting; Chen, Michael S.
Highlights Taiwan implemented PharmaCloud to provide medication records to health providers. PharmaCloud has reduced pharmaceutical expense and medication duplications. PharmaCloud is effective because the health system is universal and comprehensive. An interoperable HIS can facilitate innovations in healthcare delivery.